Translation Techniques In The Movie Script ‘Encanto’ - Ema Yanda Sari; Mayasari Mayasari; Zuindra Zuindra (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
This study focuses the translation techniques in the film script Encanto. The goals of this research are to determine the types of translation procedures employed in the Encanto Movie Script, as well as to assess how these approaches are applied. Because study is conducted using sentences and clauses, the researcher employed qualitative research methodologies. The information was obtained from the Disney Hot Star App subtitle for the film "Encanto". The researcher collected data using Molina and Albir's (2002) theory. Data obtained by reading the script in both English and Indonesian, recognizing the data, categorizing the data, evaluating the data, and drawing conclusions.The researcher discovered 136 data. there were: Literal translation, Establish Equivalent, Linguistic Compression, Borrowing, Calque, Adaptation, Compensation